Extraction of Collagen from the Skin of Kacang Goat and Production of Its Hydrolysate as an Inhibitor of Angiotensin Converting Enzyme - T. R. Hakim; A. Pratiwi; Jamhari Jamhari; N. A. Fitriyanto; Rusman Rusman; M. Z. Abidin; D. N. Matulessy; Y. Erwanto (Tropical Animal Science Journal, 2021)
The study was designed to determine the potential of collagen hydrolysate produced from the skin of Kacang goat through chymotrypsin hydrolysis to be used as an inhibitor of angiotensin converting enzyme (ACE). This research was conducted in three replications, with the measured parameters include ACE inhibitory potential and collagen hydrolysate fractionation. The results showed that collagen extraction of Kacang goat skin by chymotrypsin hydrolysis yielded 9.74% (dry matter, v/v) collagen, with pH at 6.6. The extracted collagen contained α1, α2, and β collagen chains with molecular weights of 151 kDa, 141 kDa, and 240 kDa, respectively. Furthermore, the collagen hydrolysis produced protein peptides confirmed at molecular weights of 43 to 107 kDa. The hydrolysate fractionation at molecular weights of <3 kDa, 3-5 kDa, and >5 kDa showed proteins concentrations of 2.33 mg/mL, 3.81 mg/mL, and 3.93 mg/mL, respectively. The hydrolysate fractionation with molecular weight <3 kDa showed to have ACE inhibition activity with the IC50 value of 0.47 mg/mL. The study concluded that collagen hydrolysate extracted from the skin of Kacang goat had a promising potential as a source of antihypertensive agent.